Data for: Halogens in serpentinites from the Isua supracrustal belt, Greenland: an Eoarchean seawater signature and biomass proxy? ... - D'Andres, Joëlle (Mendeley, 2020)
This dataset contains whole rock major and trace element geochemistry, mineral chemistry, zircon U-Pb isotopes and trace element data, as well as noble gases and halogens concentrations of Eoarchean serpentinites from the Isua supracrustal belt. ...